The Experimental of Impact of Additional Magnetic Fields and Nitrogen Pressure on Olive Oil Droplet Combustion - Dony Perdana (Indonesian Journal of Applied Research (IJAR), 2023)
This experiment studies the impact of a magnetic field of attraction and various nitrogen pressures in the combustion chamber on the characteristics of the flame. To replace depleted fossil fuels, the usage of vegetable oil is crucial. This research aims to probe the droplet combustion of olive oil on evolution, temperature, height, and ignition delay. The camera's high speed is 120 frames per second front-facing camera records the process from the start flamed until it has extinguished. A droplet of olive oil is placed on a type K thermocouple between two magnet rods in a nitrogen-pressurized chamber—three variations of nitrogen pressure in the combustion chamber, which included 0.5, 1, and 1.5 bar. The results found that the nitrogen pressure of 0.5 bar led to evolution, and the flame stability was more stable. Moreover, the highest temperature and flame delay was shorter than the pressures of 1 bar and 1.5 bar. At a pressure of 0.5 bar, the flame evolution was 1200 milliseconds, the maximum temperature was 741 °C, and the ignition delay of 4506 milliseconds was shorter than the other two pressures. That occurred due to high nitrogen pressure inhibiting the collision reaction of the olive oil fuel vapor with air. Meanwhile, adding an attraction magnetic field can centralize oxygen and fuel molecules in the area of the reaction zone, resulting in rapid combustion and a shorter flame delay change.